Towards a model to estimate the reliability of large-scale hybrid supercomputers - Rojas, Elvis (2020)
Supercomputers stand as a fundamental tool for developing our understanding of the universe. State-of-the-art scientiﬁc simulations, big data analyses, and machine learning executions require high performance computing platforms. Such infrastructures have been growing lately with the addition of thousands of newly designed components, calling their resiliency into question. It is crucial to solidify our knowledge on the way supercomputers fail. Other recent studies have highlighted the importance of characterizing failures on supercomputers. This paper aims at modelling component failures of a supercomputer based on Mixed Weibull distributions. The model is built using a real-life multiyear failure record from a leadership-class supercomputer. Using several key observations from the data, we designed an analytical model that is robust enough to represent each of the main components of supercom-puters, yet it is ﬂexible enough to alter the composition of the machine and be able to predict resilience of future or hypothetical systems.